CONSUMER MOTIVATIONS OF INDIAN YOUTH TO PURCHASE LUXURY BRANDS - KAPOOR, RIYA (2017)
The concept of luxury is not new in India it has been prevalent since the ancient times of maharajas, royalties and the elite classes of India who consumed luxury products throughout history. It is only in the last few decades that India has went through a dynamic economic growth this resulted in the rise of its middle class increasing their disposable income which has led to the consumption of luxury by the masses, this along with India’s massive young population has put the country on the global map of the luxury consumption market. This qualitative research studies the motivations of young Indian consumers to purchase luxury brands and what are the factors that determine the consumer behaviour of luxury brands purchase in the context of the Indian consumer sensibility. This study has explored the body of luxury literature that is focused on Western as well as the Indian consumers and has been able to present some of the similarities and differences between the Western consumers and their Indian counterparts. The findings have revealed that Product and Brand Efficacy, Appraising Interpersonal Influence, Apprehended Personal Influence, Social Class Representation and Aspirational Group Behaviour Duplication are the five basic factors that motivates the Indian consumers in their social and cultural context to purchase luxury brands.